The challenges of post-apartheid South Africa : conclusions and papers presented at a conference of the Africa Leadership Forum - Mosha, Felix G.N.; Africa Leadership Forum (Windhoek, Namibia : Africa Leadership Forum, 1991)
The conference paper addressed three major dimensions of a post-apartheid era, namely: the political implications; the strategic implication; and the economic implications. This study contains the statements and papers which were presented at the conference.
Includes bibliographical references.
ne 06/11/2019
Loans
Keywords: Politics and government; Apartheid; Economic history; South Africa